Legitimizing Military Growth and Conscription: The Yom Kippur Mechanism. Issue 3 (July 2019) - Safrai, Mordechai Zvi
By the 1970s, it was clear to the western world that the days of mass armies, based on broad conscription, were over. In Israel, however, despite the presence of some elements similar to those which elsewhere were leading to military contraction and a transition to all-volunteer forces, the Israel Defense Force (IDF) broadened its conscription model and embarked on massive growth. The effects of this surprising strategy are evident to this day, with Israel remaining almost the only conscription-based army in the West. Analysis of the organizational discourse and processes within the IDF in the wake of the Yom Kippur War reveals that social legitimacy is not only a prerequisite for organizational growth and boosting of enlistment but also, simultaneously, a product of the process. The organizational mechanisms used by the IDF to achieve social consent are relevant for an understanding of the processes of militarism and military buildup in our times, too.